"Portugizac Mlado vino" is the aroma of younger red wine more attractive? - Alpeza, Ivana; Lukić, Katarina, prehrambena biotehnologinja; Linke, Ivna; Kovačević Ganić, Karin (2021)
"Portugizac Mlado vino" is a local red wine with Protected designation of origin and Traditional term, and it is usually consumed very soon after alcoholic fermentation as a young wine. The maturation and aging of the wine affect the aroma composition, which is generally not pronounced and specific in the case of most red wines, but, as a sensory property, it is important for the perception of quality and consumer choice. The objective of this work was to analyze the most important aroma compounds of esters and higher alcohols, with the unpleasant volatile phenols too, in "Portugizac" wines, related to aging. The 9 young wines "Portugizac", PDO "Plešivica" were analyzed after 3 and after 15 months of bottle storage at 16 ºC. Ethyl esters of butanoic and hexanoic acid along with isoamyl acetate are considered to be the most important esters in the fruity aroma of wine, and their concentrations in all analyzed "Portugizac" young wine samples were higher than their perception thresholds. The concentration of ethyl acetate was in the range 30-123 mg/L. The concentrations of ethyl esters of octanoic and decanoic acid, as well as 2-phenyl ethyl acetate and diethyl succinate in all analyzed wines, were lower than their perception thresholds. The concentrations of higher alcohols were much higher than their perception threshold. Bottle storage significantly affected the concentrations of analyzed compounds; after 15 months, the concentrations of acetate and ethyl esters (except ethyl acetate and diethyl succinate), as well as terpene (linalool), decreased, while higher alcohols and ethyl phenols slightly increased if compared to three months. In general, the compounds responsible for the desired fresh, fruity aroma tones were altered in an undesirable manner, while, undesirable compounds of 4-ethyl-phenol and 4-ethyl-quaiacol, which were not present in young wines, were detected in aged wines.
"Portugizac Mlado vino" je lokalno vino sa zaštićenom oznakom izvornosti i tradicionalnim izrazom, te se obično konzumira kao mlado vino, odmah nakon alkoholne fermentacije. Dozrijevanje i odležavanje vina utječe na sastav i aromu koja u slučaju crnih vina uobičajeno nema posebnu prepoznatljvost i specifičnost, ali je kao senzorno svojstvo jako važna za percepciju kakvoće i potrošački izbor. Cilj ovog rada bio je analizirati najvažnije hlapljive spojeve estera i viših alkohola, te nepoželjnih hlapljivih fenola u mladim vinima Portugisca, u odnosu na vrijeme dozrijevanja vina u boci. Devet mladih vina "Portugizac", zaštićene oznake izvornosti "Portugizac Plešivica", s tržišta, analizirano je dva puta; 3 mjeseca i 15 mjeseci nakon punjenja u boce. Sadržaj etil estera butanske (maslačne) i heksanske (kapronske) kiseline zajedno sa izoamil acetatom, kao najvažnijih spojeva nositelja voćne arome bio je veći od praga senzorne prepoznatljivost u svim analiziranim vinima. Koncentracije etil acetata bile su u rasponu 30-123 mg/L. Koncentracije etil estera oktanske (kaprilne) i dekanske (kaprinske) kiseline, kao i 2-feniletil acetata i dietil sukcinata bile su ispod praga prepoznatljivosti u svim uzorcima. Koncentracije viših alkohola bile su značajno veće od pragova senzorne prepoznatljivosti. Čuvanje vina u boci značajno je utjecalo na promjene koncentracija analiziranih spojeva; 12 mjeseci nakon prve analize, koncentracije acetata i etil estera (osim etil acetata i dietil sukcinata), kao i terpena linalola su bile manje, dok su koncentracije viših alkohola i etil fenola bile veće nego u mladim vinima nakon prve analize. Sadržaj spojeva odgovornih za svježu, poželjnu voćnu aromu dozrijevanjem je promijenjen u neželjenom smjeru, te su utvrđeni i nepoželjni spojevi etil fenoli koji nisu bili prisutni u mladim vinima.
Bibliografija: str. 85-86.
Summary ; Sažetak.
Keywords: Portugizac; Vino -- Mlado vino -- Aroma -- Dozrijevanje u boci